Application of Leaf Fertilizer Using Nano Technology To Read Vegetative Growth of Vanda sp. - Dwi Zulfita; Maulidi Maulidi; Agus Hariyanti (Journal of Tropical Horticulture, 2019)
This study aims to find the best fertilizer concentration of Growmore leaves to stimulate vegetative growth of Orchid Vanda sp. The study was conducted at the Tanjungpura University Faculty of Agriculture's experimental garden screen house and took place from March 5 2018 to July 12, 2018. The research design used was a Completely Randomized Design with one treatment factor namely Growmore Leaf Fertilizer concentration (D) with 5 levels of treatment namely Concentration 1 g/liter of water (d1), 2 g/liter of water (d2), 3 g/liter of water (d3), 4 g/ liter of water (d4) and 5 g/liter of water (d5). Each treatment was repeated 5 times. The variables observed were the increase of number of leaves (strands), the increase of leaf length (cm), the increase of number of roots (strands) and the increase of root length (cm). The results shows that the application of Growmore fertilizer in the amount of a concentration of 1 g/ liter of water, 2 g /liter of water, 3 g/liter of water and 4 g /liter of water show an increase in the number and length of leaves of Vanda sp. which is just as good. The Growmore fertilizer concentration is the best for the number of roots and the length of the roots of Vanda sp. Orchid seeds in the amount of 3 g/liter of water.